Variations in locomotor intensities across soccer match halves concerning player sectorial positions - Élvio Rubio Gouveia; Cíntia França; Ricardo Henriques; Francisco Santos; Rui Mâncio; Krzysztof Przednowek; Hugo Sarmento (Termedia Publishing House, 2024)
Purpose This study aims to explore disparities in locomotor metrics such as total distance (TD), high-speed running (HSR), accelerations (Acc), decelerations (Dec), and maximum speed (MS) across five soccer positions - centre defenders, fullbacks, midfielders, wingers, and forwards - during the 1-, 3-, and 5-minute match intensity periods (MIP). Additionally, it seeks to assess the difference in those locomotor metrics between the first and second halves of the match. Methods An observational, retrospective cohort study was undertaken with a professional team covering 32 official matches. A total of 20 soccer players participated in this study. Data were collected using a 10-Hz GNSS unit (Apex pro series, StatSports, Northern Ireland). The MIP considered different time durations (1, 3, 5 min in the 1st and the 2nd halves). Results Soccer players exhibited position-specific differences in locomotion, with Wingers covering the most distance and forwards showing the highest Acc and Dec. HSR was most notable in the fullbacks. The second half saw varied changes, with midfielders increasing in distance covered. ANCOVA revealed significant positional differences in TD during longer MIPs and between match halves. HSR varied across positions but only differed between halves in the 5-minute MIP. Acc and Dec displayed half-time differences, while maximal speed was consistently higher in the second half. Conclusions This study highlights the impact of player position and matches progression on locomotor metrics in soccer, underscoring the need for customised training and strategic adaptability to maximise performance throughout the game.